Workshops for the Handicapped an Annotated Bibliography. Number 4 - Stubbins, Joseph, Comp.; Hadley, Robert G., Comp.; California State Coll., Los Angeles. Rehabilitation Counseling Program ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
The bibliography lists 114 annotated entries on workshops for the handicapped. Although some items date back to 1963, most are from 1966 and 1967. Research, project, and conference reports are cited as well as program descriptions and other varied publications. The three previous issues of this bibliography on workshops contain abstracts of items published through June 1966. Issues 2 and 3 are available as ED 013 005 and ED 012 543. (JD)
Availability: National Association of Sheltered Workshops and Homebound Programs, Inc., 1522 K Street, N.W., Washington, D.C. 20005 ($1.00).
Sponsoring Agency: Vocational Rehabilitation Administration (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Annotated Bibliographies; Disabilities; Exceptional Child Services; Program Descriptions; Rehabilitation; Rehabilitation Centers; Research Projects; Sheltered Workshops; Vocational Rehabilitation; Workshops